2022
DOI: 10.7717/peerj.13143
|View full text |Cite
|
Sign up to set email alerts
|

The effect of delirium information training given to intensive care nurses on patient care: quasi-experimental study

Abstract: Background Training programs aiming to improve delirium diagnosis and management skills increase nurses’ care efficiency and improve patients’ health outcomes. This study was conducted to examine the effect of delirium information training on patient care by intensive care nurses. Methods In the research, one group pretest-posttest quasi-experimental design was used. The study sample consisted of 30 nurses working in four intensive care units of a university hospital between November 05, 2018, and February 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
3
0
0
Order By: Relevance
“…This study found that engagement in training about delirium was more likely to have an association with good knowledge, which is consistent with previous studies ( 30 , 32 , 33 ). A study conducted in Poland found that lack of education about delirium control had negative effect on knowledge of delirium symptoms, risk factors and complications associated with delirium in ICU patients ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study found that engagement in training about delirium was more likely to have an association with good knowledge, which is consistent with previous studies ( 30 , 32 , 33 ). A study conducted in Poland found that lack of education about delirium control had negative effect on knowledge of delirium symptoms, risk factors and complications associated with delirium in ICU patients ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…The composition of study participants regarding of profession, in-service training, measurement tool, and sample size might also be possible reasons for the differences in knowledge and attitude level. This study found that engagement in training about delirium was more likely to have an association with good knowledge, which is consistent with previous studies (30,32,33). A study conducted in Poland found that lack of education about delirium control had negative effect on knowledge of delirium symptoms, risk factors and complications associated with delirium in ICU patients (34).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation